Re-evaluating the international tourists’ experience of local Malaysian food: what made them come back for a second taste? - Saad, Mazni; Abdul Rahman, Nadhirah; Umadi, Muhammad Fikri (Association of Malaysian Environment-Behaviour Researchers (AMER); ABRAmalaysia, Universiti Teknologi MARA, Shah Alam, 2018)
Malaysia is popular among gastronomy tourists where many of international travellers visit the country—besides other reasons—to try a diverse range of food offered by the multi-ethnic food vendors. About 17% of 26.76 million tourist arrivals in 2016 spent on food. The focus of this study is to get an insight into the tourists’ experience and evaluate the elements of experience that would lead to their revisit to the local food vendors. The study of purchase intention, aimed as a measure of the potential return visit of international tourists to the country, could benefit the tourism industry and the country’s foreign exchange.